Application of Analytical Hierarchy Process (AHP) in Educational Planning for Effective Decision Making in Senior High School - Ibrahim, Hagar Ali Marzouk (Edu Learning, 2025)
This study is conducted to evaluate the application of Analytic Hierarchy Process (AHP) in helping XII grade students at SMA Negeri 1 Tarik in choosing a college major that suits their interests and talents. The methods used include observation and application of AHP that identifies priorities based on internal and external factors through supporting tools such as Google Form and Microsoft Excel. The results showed that AHP can simplify the decision-making process, reducing the mismatch between students’ choices and their abilities.It is recommended that all stakeholders, including teachers, students, and parents, be actively involved in continuous evaluation and improvement. Regular training on the use of the AHP Online System application also needs to be conducted to improve understanding in the use of technology. With these steps, it is expected that decision-making regarding the selection of majors will be more accurate and focused on improving the quality of education as well as students’ learning outcomes, making it relevant to their potential and future goals.